A new species of Eucyclops Claus (Copepoda: Cyclopoida) from Southeast Mexico with a key for the identification of the species recorded in Mexico - Suárez-Morales, E. (Zootaxa, 2004)
Eucyclops torresphilipi sp. nov. is described from samples collected in the state of Chiapas, on the southeastern Pacific coast of Mexico. It belongs to a group of species similar to the presumably cosmopolitan E. agilis (Koch, 1838). The new species is closest to the South American E. delachauxi (Kiefer, 1925); it can be distinguished from its congeners by a combination of characters that include a fifth leg with a particularly slender inner spiniform seta that is as long as the outer seta, the caudal rami has spinules covering up to of the outer margin, caudal rami over 4 times longer than wide, the relative length of the dorsal seta, and the proportion of the terminal spines of the third exopodal segment of the fourth legs. Only nine other nominal species of Eucyclops have been recorded in Mexico; nearly half of them are known also from South America. The new species seems to have a restricted distributional range; however, it could be present also in Guatemala. Its morphological affinity with South American forms confirms the influence of the South American cyclopoid fauna in Mexico. A key for the identification of the species of Eucyclops recorded in Mexico is included.